Direct detection of nearby habitable zone planets using slicer based integral field spectrographs and epics on the E-ELT - Salter, G; Thatte, N; Tecza, M; Clarke, F; Kasper, M (Cambridge University Press, 2012)
Early design studies for the future Exo-Planet Imaging Camera and Specrotgraph (EPICS) on the European Extremely Large Telescope (E-ELT) show the ability to probe the region of super-Earths in the habitable zone of stars within 5pc (including Gilese 581d). However, these planets will be lost to us if the correct choice of integral field spectrograph (IFS) technology is not selected for such an instrument the ability to fit and remove the speckle noise that remains is crucial to reaching these contrasts. We conclusively demonstrate, though the use of an experimental setup producing an artificial speckle, that slicer based IFSs and post-processing using spectral deconvolution can achieve speckle rejection factors exceeding 103. Contrary to popular belief, we do not find any evidence that this choice of IFS technology limits the achievable contrast. Coupled with extreme adaptive optics and high performance coronographs, a slicer based integral field spectrograph could achieve contrasts exceeding 109, enabling these super-Earths to be detected in the habitable zone of nearby stars, making it an attractive option for the next generation of instruments being designed for the direct detection of extra solar planets. Copyright © International Astronomical Union 2014.